2008
DOI: 10.1002/macp.200800386
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Protonation on the Optical Properties of Conjugated Fluorene–Pyridine Copolymers

Abstract: A series of conjugated alternating and statistical copolymers of fluorene and pyridine are synthesized and characterized. The compounds under investigation, namely poly[2,7-(9,9-dihexylfluorenyl)-alt-(2,6-pyridinyl)] and poly[2,7-(9,9-dihexylfluorenyl)-stat-(2,6-pyridinyl)], are prepared by a Suzuki-type cross-coupling reaction starting from commercially available materials utilizing the recently described catalyst trans-bis(dicyclohexylamine) palladiumdiacetate (''DAPCy''). The target compounds are investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…In addition, the lowest energy absorption band is assigned to an ICT complex . The absorption maxima are comparable with those of PFs containing only 2,6‐pyridinyl, or TPA, , moieties in the main chain, but P1 and P2 exhibit a shoulder at 434 nm, in addition. The low intensities of these peaks indicate a weak oscillator strength of the ICT absorption bands and hence a small probability for the S o → 1 CT transition.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…In addition, the lowest energy absorption band is assigned to an ICT complex . The absorption maxima are comparable with those of PFs containing only 2,6‐pyridinyl, or TPA, , moieties in the main chain, but P1 and P2 exhibit a shoulder at 434 nm, in addition. The low intensities of these peaks indicate a weak oscillator strength of the ICT absorption bands and hence a small probability for the S o → 1 CT transition.…”
Section: Resultsmentioning
confidence: 79%
“…The redshift of the emission upon protonation has also been observed for other Py-containing polymers. 36,43 This emission may be attributed to the stabilization of the charge transfer state as the electronacceptor properties of Py are enhanced upon protonation. This is reasonable since only protonation of Py is expected.…”
Section: Photophysical Characterizationmentioning
confidence: 99%
“…It is known from literature that polymers containing pyridine units,27 vinylene units28 or distinct end‐chain groups29 may be prone to degrade in an acidic environment. Therefore all copolymers have been tested for the possible influence of PEDOT:PSS to the emissive spectrum, and in particular that of the PSS‐rich phase at the interface.…”
Section: Electro‐optical Properties Of Single‐ and Multilayer Devicesmentioning
confidence: 99%
“…In a previous study, Slugovc et al . reported that polyfluorene containing a pyridine ring showed pH‐dependent photoluminescence quenching and red‐shift of the emission peaks by charge transfer from fluorene units to pyridine units due to the protonation of the pyridine rings in solution . Thus, changes of fluorescence spectra suggested that the decrease of the fluorescence intensity could be attributed to the intra‐molecular charge transfer from the electron‐donor phenylene ethynylene units to the electron‐acceptor protonated pyridine units upon pH change.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that the control of and changes of the spectroscopic properties of PPyPE could be achieved by protonation of pyridine units in the polymer (38,39). (40). Thus, changes of fluorescence spectra suggested that the decrease of the fluorescence intensity could be attributed to the intra-molecular charge transfer from the electron-donor phenylene ethynylene units to the electronacceptor protonated pyridine units upon pH change.…”
Section: Protonation Of Ppype By Hydrochloric Acidmentioning
confidence: 90%